2019
DOI: 10.1515/hsz-2019-0170
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin is required for normal accumulation of body fat

Abstract: Intermediate filaments (nanofilaments) have many functions, especially in response to cellular stress. Mice lacking vimentin (Vim−/−) display phenotypes reflecting reduced levels of cell activation and ability to counteract stress, for example, decreased reactivity of astrocytes after neurotrauma, decreased migration of astrocytes and fibroblasts, attenuated inflammation and fibrosis in lung injury, delayed wound healing, impaired vascular adaptation to nephrectomy, impaired transendothelial migration of lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
4
20
0
Order By: Relevance
“…Our in vitro data were further confirmed by direct observation of lipid distribution defects in zebrafish (Fig. 6e, f ), which is reminiscent of the fat accumulation defects observed in vimentin KO mice [ 8 ]. The increase in lipodystrophy upon injection of wt vimentin mRNA is compatible with the notion that transgenic overexpression of wt vimentin caused pathological anomalies in mice [ 34 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our in vitro data were further confirmed by direct observation of lipid distribution defects in zebrafish (Fig. 6e, f ), which is reminiscent of the fat accumulation defects observed in vimentin KO mice [ 8 ]. The increase in lipodystrophy upon injection of wt vimentin mRNA is compatible with the notion that transgenic overexpression of wt vimentin caused pathological anomalies in mice [ 34 ].…”
Section: Discussionsupporting
confidence: 80%
“…This organ-specific disease was surprising, considering the wide tissue expression of vimentin. In line with this unexpected phenotype, the targeted deletion of vimentin in mice caused widespread but mild phenotypes in unchallenged animals [ 2 , 8 ]. Most recently, the analysis of phospho-deficient vimentin knockin mice indicated a role of vimentin in skin aging, neuronal differentiation, and subcutaneous fat loss [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In adipose, the top 3 significant GO pathways of ASE genes include 'fatty acid metabolic process' (P = 7.24×10 -9 ), 'acylglycerol metabolic process' (P = 6.31×10 -8 ) and 'regulation of cholesterol metabolic process' (P = 8.13×10 -7 ) (Supplementary Figure S9A, Manuscript to be reviewed metabolism of long-chain fatty acids and has been proved to have a close relationship with carcass back fat thickness and intramuscular fat contents (Cho et al, 2011). VIM encodes a type III intermediate filament protein and is required for the normal accumulation of body fat (Wilhelmsson et al, 2019). ACSL1 encodes an isozyme of the long-chain fatty-acid-coenzyme A ligase family and functions in converting free long-chain fatty acids into fatty acyl-CoA esters; a previous study suggested this gene might contribute to the capacity of fat deposition and meat quality in pig breeds (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These in vitro studies support the hypothesis that vimentin is involved in obesity and type 2 diabetes mellitus. A recent study reported that vimentin-null mice on a chow diet have lower body weight and less body fat com-pared with wild-type mice, suggesting a role of vimentin in normal accumulation of body fat [9]. However, there have been no animal studies verifying the role of vimentin in highfat diet (HFD)-induced obesity and type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%